AML1–ETO triggers epigenetic activation of early growth response gene l, inducing apoptosis in t(8;21) acute myeloid leukemia. (10th January 2014) - Fu, Lin; Huang, Wenrong; Jing, Yu; Jiang, Mengmeng; Zhao, Yu; Shi, Jinglong; Huang, Sai; Xue, Xue; Zhang, Qingyi; Tang, Juying; Dou, Liping; Wang, Lili; et al.
<x xml:space="preserve">Abstract</x> The t(8;21)(q22;q22) translocation is the most common chromosomal translocation in acute myeloid leukemia (AML), and it gives rise to acute myeloid gene 1 (AML1)–myeloid transforming gene 8 (ETO)‐positive AML, which has a relatively favorable prognosis. However, the molecular mechanism related to a favorable prognosis in AML1–ETO‐positive AML is still not fully understood. Our results show that the AML1–ETO fusion protein triggered activation of early growth response gene l (EGR1) by binding at AML1‐binding sites on the EGR1 promoter and, subsequently, recruiting acetyltransferase P300, which is known to acetylate histones. However, AML1–ETO could not recruit DNA methyltransferases and histone deacetylases; therefore, EGR1 expression was affected by histone acetylation but not by DNA methylation. Both transcription and translation of EGR1 were higher in AML1–ETO‐positive AML cell lines than in AML1–ETO‐negative AML cell lines, owing to acetylation. Furthermore, when AML1–ETO‐positive AML cell lines were treated with C646 (P300 inhibitor) and trichostatin A (histone deacetylase inhibitor), EGR1 expression was significantly decreased and increased, respectively. In addition, treatment with 5‐azacytidine (methyltransferase inhibitor) did not cause any significant change in EGR1 expression. Overexpression of EGR1 inhibited cell proliferation and promoted apoptosis, and EGR1 knockout promoted cell proliferation. Thus, EGR1 could be a novel prognostic factor for a favorable outcome in AML1–ETO‐positive AML. The results of our study may explain the molecular mechanisms underlying the favorable prognosis in AML1–ETO‐positive AML.